IMPLEMENTASI STRATEGI PENGEMBANGAN KEPARIWISATAAN - Diana Persari; Meyzi Heriyanto; Febri Yuliani (Universitas Riau, 2018)
Implementation of Tourism Development Strategy. This study aims to find out,analyze and to find out the supporting and inhibiting factors that influence the Implementation ofthe Tourism Development Strategy of the Sultan Riau Mosque of Penyengat Island. This type ofresearch is qualitative descriptive research. Data collection by observing interviews anddocumentation with selected informants consisting of the Head and Staff of the Office of Cultureand Tourism, Mosque Management, Malay Customary Institution, Tourism Awareness Group andTourists. The results of the study concluded that the implementation of the tourism developmentstrategy of Sultan Riau Grand Mosque from program indicators, resources and procedures was notoptimal because there were still inhibiting factors for the implementation of tourism developmentstrategies such as facilities and infrastructure, budget, human resources, not optimal synergy andpartnership, but still there are supporting factors that must be optimized by the Tanjungpinang CityTourism and Culture Office, the regional strategic position, the potential for cultural diversity, thedevelopment of tourist market trends, and the opening of opportunities for cooperation.